PARTISIPASI PEMILIH PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR BANTEN TAHUN 2024 - Mahmud, Toni Anwar; Supriyadi, Agus (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
The Simultaneous Regional Elections (Pilkada) in Indonesia aim to enhance democratic processes by increasing electoral efficiency and effectiveness. Governed by Law No. 10 of 2016, Pilkada allows citizens to directly elect regional leaders, thereby shaping local governance and development. Banten Province, characterized by its unique geographical and demographic conditions, participated in the 2024 Pilkada to elect its Governor and Deputy Governor. With a high urbanization rate, particularly in the Tangerang metropolitan area, and a diverse voter composition, the election dynamics in Banten reflect broader political trends and challenges. This study employs a qualitative approach to analyze the 2024 Banten gubernatorial election, focusing on voter participation factors and the political implications of the election results. Data collection was conducted through literature reviews of relevant books, scientific journals, official reports, and media sources. The research finds that the election was highly competitive, with two prominent candidate pairs: Airin Rachmi Diany–Ade Sumardi and Andra Soni–Achmad Dimyati Natakusumah. The election results declared Andra Soni and Achmad Dimyati Natakusumah as the winning candidates, securing 55.88% of the votes. Voter participation reached 66.19%, an improvement compared to previous elections, with Serang Regency recording the highest turnout (73.76%) and South Tangerang City the lowest (57.08%). Female voters dominated participation at 53.18%, while disabled voters had a significantly lower turnout at only 36.98%. The study suggests that election organizers, particularly the Banten Provincial General Election Commission (KPU), should conduct targeted outreach in low-turnout areas and provide better accessibility for disabled voters to enhance electoral participation in future elections.